Efektivitas Bahan Ajar Berbasis Kearifan Lokal Cerita Rakyat Joko Poleng pada Kemampuan Membaca Siswa Sekolah Dasar - Kusumah, Rita; Yani Fitriyani (Jurnal Pelita PAUD, 2024)
The understanding of students today about the existence of folklore in their own area often does not understand much, even though it is in the learning content, the presentation that is less interesting and monotonous makes students not interested and feel bored with the learning being carried ouIn this study, researchers tried to measure the effectiveness of using teaching materials based on local wisdom of the Joko Poleng folklore. The design used in this study is one group pretest posttest. So the researcher only used one group of 27 students as the research sample.This study obtained the results that students' learning when using teaching materials that were already in the theme book got an average value of 62.96 while student learning outcomes after using Joko Poleng's folklore teaching materials were 88.89. Therefore there is an increase of 25.93 from the results before and after students use teaching materials. In this case, the Joko Poleng Folklore Teaching Material is effective for use in elementary school students.This is shown from the results before and after students use teaching materials. It is also shown from the results of the analysis. It is shown from the results of data analysis that the significance value of the paired samples test for two data, namely pretest and posttest, is 0.000, because the significance value is smaller than the value of (0.05), then the hypothesis is accepted.